Animals, Capitalism, Resistance: Review of Fahim Amir, Being and Swine: The End of Nature (As We Knew It) - Wadiwel, Dinesh (Humanimalia, 2023)
Fahim Amir. Being and Swine: The End of Nature (As We Knew It). Translated by Geoffrey C. Howes and Corvin Russell Toronto: Between the Lines, 2020. 228 pp. $24.95 (pb).